Monitoring and storing of temperature and luminosity data using ZigBee sensor networks - Melo Junior, Gilberto de (2021)
The proposed article reports the development of a wireless sensor network based on the ZigBee protocol. A Coordinating device and a final device were developed to act on the network, monitoring luminosity and temperature data in an environment. The network was tested and validated by monitoring the relevant data, which in turn was presented on a web server, EmonCMS, and recorded on a Secure Digital (SD) memory card. The developed project had low energy consumption.